Group-Theoretic Description of Riemannian Spaces - Samokhvalov, S. E. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
We show that the geometric structure of an arbitrarily curved Riemannian space is locally determined by a deformed group of its diffeomorphisms.